Perancangan Alat Bawa Bertema Y2K Menggunakan Metode Trend Forecasting untuk Gen Z Saat Festival Musik - Afiff, Diza Khadijah; Waskito, Mohamad Arif (Fakultas Industri Kreatif Universitas Surabaya, 2025)
Among Gen Z, the design of fashion products often follows trends, which means it changes quickly, placing this industry in the category of fast fashion. Fast fashion can cause various problems, such as accumulating waste, and if the production process takes too long, the products may lose relevance to the trends by the time they are launched in the market. From the consumer side, particularly Gen Z, there is a preference for customizable products, making them more interested in items tailored to their wants and needs. The issues within the industry and opportunities from consumers give rise to a strategy as a solution: designing fashion items with a relevant annual theme using the Trend Forecasting Method. This strategy includes a scheduled yearly theme, ensuring that production time is more measured and planned. This reduces the risk of products becoming irrelevant due to rapidly changing trends, as specific special editions are launched with consistent momentum. The intended benefits of this research are to enhance the relevance of products with current trends while simultaneously meeting Gen Z’s preferences for more personalized and trendy fashion.